Teachers Perception in Inculcating Islamic Values in Secondary Schools - Muhammad Amin Mt; Azlina Mustaffa (International Journal of Education and Learning, 2019)
This research intended to explore the challenges in inculcating Islamic values among teachers in selected private secondary schools in the Klang Valley. It aimed to investigate the teachers’ perception in inculcating Islamic values in schools. The questionnaire was distributed to 145 teachers from three private Islamic secondary schools in the Klang Valley, namely Al-Amin secondary school, International Islamic Secondary (IIS) School and ADNI Islamic Secondary School. A 5-point Likert scale was used to measure the teachers’ perception about the inculcating Islamic values in schools. Descriptive analysis (frequencies and percentages), were utilized in this study. The findings showed that most of the teachers in the three schools in the Klang Valley perceived that they are not inculcating Islamic values into their teaching. The researcher suggested that future research should include additional Islamic schools to compare their methods of teaching Islamic studies, which can also include universities.